Closed-loop liquid-liquid immiscibility in mixture of particles with spherically symmetric interaction - Kalyuzhnyi, Yu.V.; Hvozd, T.V. (Condensed Matter Physics, 2013)
Thermodynamic perturbation theory for cetral-force (TPT-CF) type of associating potential is used to study the phase behavior of symmetric binary mixture of associating particles with spherically symmetric interaction. The model is represented by the binary Yukawa hard-sphere mixture with additional spherically symmetric square-well associative interaction located inside the hard-core region and valid only between dissimilar species. To account for the change of the system packing fraction due to association we propose an extended version of the TPT-CF approach. In addition to already known four types of the phase diagram for binary mixtures we were able to identify the fifth type, which is characterized by the absence of the intersection of the λ-line with the liquid-vapour binodals and by the appearance of the closed- loop liquid-liquid immiscibility with upper and lower critical solution temperatures. В рамках термодинамiчної теорiї збурень для асоцiативного потенцiалу типу центральних сил проведено дослiдження фазової поведiнки симетричної бiнарної сумiшi асоцiативних частинок з сферично-симетричною взаємодiєю. Модель представлено бiнарною сумiшшю юкавiвських твердих сфер з додатковою сферично-симетричною асоцiативною взаємодiєю типу прямокутної ями, яка розмiщена усерединi областi твердої сфери i дiє тiльки мiж рiзними сортами. Враховуючи змiну упаковки системи внаслiдок асоцiацiї, запропоновано узагальнення термодинамiчної теорiї збурень для асоцiативного потенцiалу типу центральних сил. На додаток до чотирьох вже вiдомих типiв фазових дiаграм для бiнарних сумiшей, нам вдалося визначити п’ятий тип, який характеризується вiдсутнiстю перетину лямбда-лiнiї з бiнодалями “рiдина-газ” i появою незмiшування “рiдина-рiдина” у виглядi замкненої петлi з верхньою i нижньою критичними температурами змiшування.